Environmental and toxicological concerns associated with nanomaterials used in the industries - Mir, Tahir ul Gani; Katoch, Vaidehi; Angurana, Ruby; Wani, Atif Khurshid; Shukla, Saurabh; El Messaoudi, Noureddine; Sher, Farooq; Mulla, Sikandar I.; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Elsevier, 2023)
The field of nanotechnology is receiving scientific interest and key priorities in research and development all around the world. The novel achievements in this discipline have various practical applications in domestic and industrial sectors. One of the main applications of nanotechnology is environmental nanoremediation. Nanoremediation, defined as the use of synthesized nanomaterials to clean up the environment, is a potential technique for dealing with persistent pollutants like pesticides, chlorinated solvents, halogenated chemicals, or heavy metals. Excessive use of nanotechnology, on the other hand, might result in negative consequences. The release of nanomaterials into the environment is one of the adverse consequences of the widespread use of nanotechnology. Due to the widespread usage of nanotechnology in industries, industrial waste comprising residual nanoparticles is continuously being released into the environment. The contamination of the environment with nanomaterial particulate matter may have several toxicological effects on living organisms and their habitat. After entering the body, nanoparticles may induce DNA damage, mitochondrial damage, and cell apoptosis/death in various sensitive organs, including the kidneys, lungs, and liver. This review aims to critically assess various environmental and toxicological concerns of nanomaterials. The first part of this literature review describes nanomaterials as a potential tool for environmental cleanup. The second and third part of this review describes various environmental effects and toxicities induced by the use of nanomaterials, and the last part of this review discusses microbe-assisted bioremediation of nanomaterial contaminants.
Keywords: Environment; Nanomaterials; Nanoparticles; Nanoremediation; Toxicity